A case study of the physics enhancement project for two year colleges, its effects and outcomes on the teaching of undergraduate physics at two year colleges - Leif, Todd Robert (Kansas State University, 2008)
This dissertation reports on a naturalistic evaluation study of a series of NSF grant projects collectively known as PEPTYC -- Physics Enhancement Project for Two Year College Physics Instructors. The project encompassed seven different cycles of professional development occurring during the 1990's via May Institutes, held at Texas A&M University. Follow-up meetings were held at American Association of Physics Teachers - Texas Section Meetings. The research was conducted post hoc. The research evaluated the characteristics of effective professional development under an evaluation frame work designed by D.L. Kirkpatrick (1959) and adapted by the researcher to address issues that are pertinent to the professional development of faculty. This framework was adapted to be viewed through an educator's eye in an effort to ascertain the long term affects of the program and determine how the program affected the participants' attitudes, pedagogical knowledge, and instructional practices. The PEPTYC program philosophy was based on the premise, supported by research, that professional development programs addressing specific teaching practices are more successful than generic programs. Furthermore, professional development is more effective in helping teachers use alternative approaches when teachers are engaged in active learning experiences rather than passively listening to lectures or presentations. The naturalistic study was based on surveys and semi-structured interviews with 14 individuals who participated in PEPTYC workshops, as well as presenters of the PEPTYC program. The interviews were analyzed to describe how the PEPTYC project influenced the participants long after they had completed their training. This project can inform the development of similar evaluation studies of other professional development programs.
Keywords: Physics Enhancement Project; Two year colleges; Professional development; Physics education; Education, Curriculum and Instruction (0727)